(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The scientific development that was brought by modern civilization has left its clear imprints in the field of biology, which is directly reflected on the living cell and its relationship to genetics and formation. That It has recorded many scientific discoveries in the field that provided a wide opportunity to reveal some of the secrets of the human cell. The science of cell study (cytology) is no longer limited to a purely descriptive study, but rather extended to the experimental study with the help of experimental embryology and analytical studies of the fertilization process, until the development of the scientific increases in the awareness of the major fundamental issues that are related to cytological genetics which are the nature of the human gene and self-reproduction and how to perform his work in a report about these attributes, also this development has extended to include the treatment of some genetic diseases, as this science has extended to the field of legal evidence (criminal and civil), this is because the traditional means which are used in evidence and improving may not achieve the justice or be insufficient to achieve them.